CMV Oophoritis in an AIDS Patient. Issue 5 (1995) - Albert, Michael S.; Amstey, Marvin S.
Abstract : Background: Disseminated cytomegalovirus (CMV) infection is relatively uncommon, occurring primarily in immunocompromised hosts and neonates. Patients with acquired immunodeficiency syndrome (AIDS) are the most common hosts, with symptoms secondary to lung and eye involvement. There have been no reports of symptomatic CMV infection of the pelvis in women. Case report: This case is the first described of acute symptomatic CMV infection of the genital tract in a woman with AIDS. Her presenting symptoms were the result of acute CMV oophoritis. In addition, CMV was found in the endometrium and endosalpinx (an infected structure heretofore unreported). Conclusion: The increasing prevalence and incidence of AIDS in women should make us aware of the possibility of opportunistic, symptomatic CMV pelvic infection.